COMPARATIVE ANALYSIS BETWEEN LOCAL AND EXPATRIATE CONSUMERS - Nurcahyo, Rianto; Tirani, Mustika; Pello, Kareem Abdul Jabbar (STIE Kusuma Negara, 2020)
Education is not only gained through a formal system but education can be gained through non formal ways. One kind of education that is important is Physical Education. Physical education is very important to have in both in and out of school. This shows that even though there are changes in educational curriculums, physical education is still a mandatory subject taught at schools. This research aims to determine the effect of price, location, and perceived value on purchase decision and to find out the difference of the influence of price, location, and perceived value on purchase decision between local and expatriates consumers at Little Kickers Indonesia. Survey of this research was conducted to all consumers in Little Kickers Indonesia at Kemang and Alam Sutra branch with total respondents is 82 people, with total of local and expatriate consumers for each are equal to 41. The results of this research show that price, location, and perceived value have a significant influence on purchase decision simultaneously both from local and expatriate consumers. The results of the comparative analysis show that only price variable that has significant differences which are tested between local and expatriate consumers in Little Kickers IndonesiaAbstrak ditulis dalam Bahasa Inggris. Abstrak memuat uraian mengenai tujuan penelitian, metode yang digunakan, dan hasil penelitian. Key word: Local, Expatriate Price, Perceived Value, Purchase Decision.